KEPENTINGAN INDONESIA MENJALIN KERJASAMA NON-MIGAS DENGAN AFRIKA SELATAN DALAM REGIONALISASI SOUTHERN AFRICAN DEVELOPMENT COMMUNITY (SADC) TAHUN 2015-2017 - Octavia Tri Nararanti; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research aims to analyze the non-oil and gas cooperation between Indonesia and South Africa. South Africa's economy is the third largest after Nigeria and Egypt. South Africa is one of the most important countries in the South African Development Community (SADC) in the region. SADC is a regional organization in South Africa that aims to reduce disparities in economic development in that region.In this research the authors used a qualitative research method with library research data collection techniques. The perspective used is liberalism, with the level of analysis of the nation-state. The theory used is international collaboration by K.J Holsti.Indonesia in conducting trade and investment economic relations with South Africa is to fulfill Indonesia's national interests. South Africa is the gateway for Indonesian products to SADC countries (Angola, Botswana, Democratic Republic of Congo, Lesotho, Madagascar, Malawi, Mauritius, Malawi, Mozambique, Namibia, Seychelles, Swazilan, Tanzania, Zambia and Zimbabwe). Keywords: SADC, International Cooperation, Interest, Gateway